2019
DOI: 10.5194/isprs-archives-xlii-4-w19-9-2019
|View full text |Cite
|
Sign up to set email alerts
|

Automated Prediction System for Vegetation Cover Based on Modis-Ndvi Satellite Data and Neural Networks

Abstract: Around the world, vegetation cover functioning as shelter to wildlife, clean water, food security as well as treat large part of air pollution problem. Accurate predictive data early warn and provide knowledge for decision makers to reduce the effects of changes in vegetation cover. In this paper, an automated prediction system was developed to forecast vegetation cover. Prediction system based on moderate satellite data spatial resolution and global coverage data. The tools of system automate processing Moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…NDVI values were calculated from the near infrared (band 5) and red (band 4) bands of Landsat 8 imagery to identify areas on a spectrum between −1.0 and 1.0 to represent a lack of green vegetation and dense green vegetation, respectively. Many studies have shown that NDVI values can be used to determine LULC classes and can be projected forward to forecast vegetation cover [54][55][56][57][58][59][60][61]. Landsat 8 bands for the month of January in 2015 and 2020 were used to ensure cloud free imagery with similar seasonality, and Equation (2) was used to calculate the NDVI.…”
Section: Land Use/land Cover Scenariosmentioning
confidence: 99%
“…NDVI values were calculated from the near infrared (band 5) and red (band 4) bands of Landsat 8 imagery to identify areas on a spectrum between −1.0 and 1.0 to represent a lack of green vegetation and dense green vegetation, respectively. Many studies have shown that NDVI values can be used to determine LULC classes and can be projected forward to forecast vegetation cover [54][55][56][57][58][59][60][61]. Landsat 8 bands for the month of January in 2015 and 2020 were used to ensure cloud free imagery with similar seasonality, and Equation (2) was used to calculate the NDVI.…”
Section: Land Use/land Cover Scenariosmentioning
confidence: 99%
“…The second category focused on (ii) analyzing the data generated from the interaction between the learner and the learning system (e.g., de Vicente, 2003;Qu. and Johnson, 2005;Ramaha, 2012;Ramaha, 2017;Abujayyab and Karaş, 2019), these data are usually saved by the system in a log file, these types of researches applicable for attention detection in elearning systems. However, those research approaches still inaccurate, and are complex to design and maintain.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation cover plays a critical role in sustaining life on earth by acting as a shelter for fauna, and minimizing air and water pollution (Abujayyab, Karaş, 2019). However, terrestrial ecosystems face environmental deforestation, destruction, and degradation, which are the main sources of greenhouse gas emissions (Poortinga et al, 2018) resulting from harmful anthropogenic activities (Šalić, A., and Zelić, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The local climate of an area varies with the changes and transition of vegetation cover which depends on several factors such as timing and location (Duveiller et al, 2018). The prediction of changes in vegetation cover will help to provide timely insights for decision-makers to effectively manage vegetation in a region (Abujayyab, Karaş, 2019).…”
Section: Introductionmentioning
confidence: 99%